Corporate social responsibility as a defense against knowledge spillovers: Evidence from the inevitable disclosure doctrine. (5th April 2019) - Flammer, Caroline; Kacperczyk, Aleksandra
Abstract : Research Summary: We examine whether companies respond to the threat of knowledge leakage by strategically increasing their engagement in corporate social responsibility (CSR). To obtain exogenous variation in the threat of knowledge leakage, we exploit a natural experiment provided by the rejection of the inevitable disclosure doctrine (IDD) by several U.S. states. Using a difference‐in‐differences methodology we find that, following the rejection of the IDD, companies significantly increase their CSR. Our proposed rationale is that CSR helps mitigate knowledge leakage by (i) reducing employees' propensity to join a rival firm, and (ii) reducing employees' propensity to disclose the firm's valuable knowledge even if they join a rival firm. Evidence from a laboratory experiment, an online experiment, and a survey of knowledge workers is supportive of these arguments. Managerial Summary: We study the role of CSR in companies' response to the threat of knowledge leakage—a major managerial challenge that has important implications for firms' innovation and competitiveness. We use three different research designs (an analysis of companies' CSR policies in response to an increased threat of knowledge leakage; a survey of knowledge workers; and an experiment conducted both online and in a laboratory setting). The results show that CSR is perceived to mitigate the threat of knowledge leakage. In particular, (i) CSR reduces knowledge workers' propensity to join rival firms (i.e., they are less likely to "walk") and, even if they do, (ii) CSR reduces their propensity to disclose the firm's valuable knowledge to their new employer (i.e., they are less likely to "talk").